Folic acid and zinc improve hyperuricemia by altering the gut microbiota of rats with high-purine diet-induced hyperuricemia - Sun, Xuewei; Wen, Jie; Guan, Baosheng; Li, Jialin; Luo, Jincheng; Li, Jie; Wei, Mingyu; Qiu, Hongbin (Frontiers in Microbiology, 2022)
A high-purine diet can cause hyperuricemia and destroy the microbial composition of the gut microbiota. Both folic acid and zinc significantly reduce uric acid levels and alleviate hyperuricemia. However, whether the underlying mechanisms are associated with the regulation of the gut microbiota remain unknown. To explore alterations of the gut microbiota related to folic acid and zinc treatment in rats with hyperuricemia in our study. A hyperuricemic rat model was established with a high-purine diet. The effects of folic acid and zinc on uric acid levels were evaluated. Alterations of the gut microbiota related to hyperuricemia and the treatments were evaluated by sequencing using the Illumina MiSeq system. The results demonstrated that uric acid levels dropped observably, and the activities of adenosine deaminase (ADA) and xanthine oxidase (XOD) were downregulated after folic acid or zinc intervention. 16S rRNA gene sequencing-based gut microbiota analysis revealed that folic acid and zinc enhanced the abundance of probiotic bacteria and reduced that of pathogenic bacteria, thus improving intestinal barrier function. PICRUST analysis indicated that folic acid and zinc restored gut microbiota metabolism. These findings indicate that folic acid and zinc ameliorate hyperuricemia by inhibiting uric acid biosynthesis and stimulating uric acid excretion by modulating the gut microbiota. Thus, folic acid and zinc may be new and safe therapeutic agents to improve hyperuricemia.